Co-occurrence and diversity patterns of benthonic and planktonic communities in a shallow marine ecosystem - Ríos-Castro, Raquel; Costas-Selas, Cecilia; Pallavicini, Alberto; Vezzulli, Luigi; Novoa, Beatriz; Teira, Eva; Figueras, Antonio (Frontiers in Marine Science, 2022)
Marine microorganisms are involved in a variety of biogeochemical cycles and live in diverse ecological communities where they interact with each other and with other organisms to guarantee ecosystem functions. The present study focused on a shallow marine environment located in Ría de Vigo (NW, Spain), where sediment and size-fractionated plankton samples were collected from 2016 to 2018. DNA metabarcoding was used to describe the eukaryote and prokaryote composition and diversity in sediments and plankton and to depict possible associations among the most frequent and abundant organisms by co-occurrence network analysis. High eukaryote and prokaryote diversity indices were obtained in all compartments. Significant differences among eukaryote and prokaryote communities were found between sediment and plankton samples, with a high percentage of exclusive operational taxonomic units (OTUs) associated with each compartment, especially from sediment. Despite these differences, shared taxa between water and sediment were also obtained, suggesting a relatively meaningful exchange of organisms between both environmental compartments. Significant co-occurrences were mainly obtained between prokaryotes (41%), followed by eukaryotes–prokaryotes (32%) and between eukaryotes (27%). The abundant and strong positive correlations between organisms, including representatives from the sediment and the water column, suggested an essential role of biotic interactions as community-structuring factors in shallow waters where beneficial associations likely prevail. This study provides a novel approach for the detailed description of the eukaryote and prokaryote diversity and co-occurrence patterns in a shallow marine area, including both the sediment and different water-size fractions. The high diversity obtained and the detection of predominantly coexisting interactions among organisms from sediment and the overlying water column suggest a movement of species between both habitats and therefore confirm the importance of integratively studying shallow marine ecosystems.